Perspektif Nilai Sejarah Naskah Hikayat Aceh - Hermansyah (Indonesian Journal of Islamic History and Culture, 2020)
The earliest works of literary genres during the Kingdom of Aceh Darussalam were historical literature. Historical stories and saga that tell about the figures, connections, and genealogies of the sultan's government in the Aceh kingdom. The Hikayat Aceh is one of is one of the historical texts. The text is anonym the author. This research uses a narrative analysis approach in which historical assessment is viewed inside the text of Hikayat Aceh. Inventory of manuscripts obtained three interrelated texts of Hikayat Aceh; Firstly Cod. Or. 1954, second Cod. Or 1983 are collected by the Leiden University, and the third text was written and kept at the National Library of Jakarta with code ML 421. Both of the texts are uncompleted and beginning. The Hikayat Aceh has become one of the basic historical sources of the Aceh Sultanate and describes other historical manuscripts of the same period.